Macroeconomic effects of proposed pension reforms in Norway - Dennis Fredriksen; Kim Massey Heide; Erling Holmøy; Ingeborg Foldøy Solli (Statistics Norway, Research Department, 2005)
Ageing combined with generous welfare state schemes makes the present fiscal policy in Norway unsustainable, despite large government petroleum revenues. We estimate to what extent two suggested reforms of the public pension system improve fiscal sustainability and stimulate employment, two main objectives of the reforms. To this end we apply two large models iteratively: 1) a detailed dynamic micro simulation model to estimate government pension expenditures; 2) a large CGE-model to estimate general equilibrium effects on all tax bases and employment, i.e. macroeconomic effects. We find that the reform proposals have much larger effects than typically found for reforms of the tax and trade policy. Whereas maintaining the present system implies that the payroll tax rate must be increased from about 13 percent today to 25 percent in 2050, both proposals imply that taxes can be reduced from the present level in all years up to 2050. Most of this reduction can be attributed to higher employment.
Keywords: H30; H55; H62; 330; Population ageing; Fiscal sustainability; Pension reforms; Computable general equilibrium model; Dynamic micro simulation